WAHO/ROPPA/Bioversity International regional initiative for the promotion of local foods from the biodiversity of West Africa's traditional food systems: Report of a regional workshop of small-scale farmer organizations, researchers, and representatives from regional and international organizations 3-5 November, 2009, Ouagadougou, Burkina Faso - West African Health Organization; Réseau des Organisations Paysannes et des Producteurs Agricole de l'Afrique de l'Ouest; Bioversity International (2010)
Dietary diversification is vital to tackling the problems of hunger, micronutrient malnutrition and diet-related chronic diseases.Reports show that the increasing nutrition and health problems of population groups in West Africa are paralleled by the decline in the use of foods from the traditional food systems, and by the loss of indigenous knowledge, essential for the full exploitation of these food resources that have positive nutrition and health benefits. This publication is the report of the three days workshop organized in collaboration with WAHO, ROPPA and Bioversity International with the objective to bring together pivotal players and key experts from relevant sectors to brainstorm and map out concrete actions to be undertaken in order to achieve increases in the production, marketing, availability and accessibility, and consumption of nutrient-rich foods from West Africa’s traditional food systems by rural and urban households.